A cadeira de história e filosofia da educação da USP entre os anos 40 e 60: um estudo das relações entre a vida acadêmica e a grande imprensa - Bontempi Júnior, Bruno (2001)
This work intends to conduct a study on the relations between the university, the intellectuals, the academic discipline and the mainstream press, focusing its analysis on the Subject of History and Philosophy of Education at the College of Philosophy, Sciences and Literature of the University of São Paulo between the 1940's. and the 1960's.With the purpose of overcoming the reach of the "internalist" investigations on academic disciplines, which generally limit themselves to find the chain that links predecessors and successors and to check their evolution within an internal economy, this study seeks to inscribe it in an articulate set, consisting of the intellectual thinker Laerte Ramos de Carvalho, who acted as its regent for several years, the University of São Paulo and the newspaper O Estado de S. Paulo. The aim of this operation is to "recreate" the environment which configures the interests and guide lines adopted by Ramos de Carvalho while organizing and directing it is considered the first academic project to write the history of the Brazilian education